Influences of the geogrid-reinforced soil platform on the performance of pile-supported embankment - Zhao, Zhihui; Zheng, Leiming (Frontiers in Earth Science, 2024)
Geosynthetic-reinforced pile-supported embankments have seen widespread adoption worldwide in recent years due to their cost-effectiveness and construction efficiency. In this system, the conventional pile cap is replaced by the geogrid-reinforced soil platform (GRSP), which enhances horizontal load transfer to stabilize the embankment. This study investigates the influences of GRSP on the behavior of pile-supported embankments through field testing and numerical computation. The measured results of field testing indicate that a well-compacted GRSP reduces the lateral displacement of the embankment and changes the development of pressures acting on pile and soil. Numerical analysis demonstrates that both soil arching and tensioned membrane effects effectively transfer loads from the soil to the piles, with the tensioned membrane effect typically being more prominent. The characteristics of the GRSP have a significant impact on both effects, with elastic modulus, tensile stiffness, and friction angle being the three most crucial parameters for reducing embankment settlement.